FEATURES OF THE CLINICAL COURSE OF CHRONIC RECURRENT APHTHOUS STOMATITIS - Mirvakhidova Nazokat.M (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. Chronic recurrent aphthous stomatitis is one of the most widespread diseases of the oral mucosa. The prevalence of recurrent aphthous stomatitis, according to various authors, ranges from 10 to 40% in different age groups of the population. Over the past 10 years, there has been a marked trend towards an increase in the number of patients with recurrent aphthous stomatitis, and with its severe form. Recurrent aphthous stomatitis occurs against the background of sensitization of the body to conditionally pathogenic microorganisms of the oral cavity, viruses, food or microbial allergens. Studies have shown that bacterial allergies develop in patients with dysbiosis of the distal gastrointestinal tract.